Body mass index in individuals with HIV infection and factors associated with thinness and overweight/obesity Índice de massa corporal em indivíduos com infecção pelo HIV e fatores associados com magreza e sobrepeso/obesidade - Carolline de Araújo Mariz; Maria de Fátima P. Militão de Albuquerque; Ricardo Arraes de Alencar Ximenes; Heloísa Ramos Lacerda de Melo; Francisco Bandeira; Thaís Gelenske Braga e Oliveira; Érico Higino de Carvalho; Adriana Paula da Silva; Demócrito de Barros Miranda Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
A cross-sectional study was conducted using body mass index (BMI) to estimate the prevalence of thinness and overweight/obesity and associated factors in 2,018 individuals with HIV/AIDS attending health services referral centers. The dependent variable was classified as thinness, overweight/obesity and eutrophy. Multinomial logistic regression analyses were performed considering eutrophy as the reference level. The prevalence of thinness was 8.8% and of overweight/obesity, 32.1%. The variables associated with thinness were anemia and CD4 cell count < 200mm³. The variables associated with risk of overweight/obesity were age > 40 years and diabetes, and the variables identified as decreasing likelihood of overweight/obesity were having no long-term partner, smoking, presence of an opportunistic disease, anemia, and albumin levels < 3.5mg/dL. The main nutritional problem observed in this population was overweight and obesity, which were much more prevalent than thinness. Older individuals with diabetes should be targeted for nutritional interventions and lifestyle changes. Estudo seccional para estimar a prevalência de magreza e sobrepeso/obesidade e fatores associados em 2.018 indivíduos com HIV/AIDS, atendidos em serviços de referência em Recife, Pernambuco, Brasil, utilizando o índice de massa corporal. A variável dependente foi classificada como magreza, sobrepeso/obesidade e eutrofia. Realizou-se análise de regressão logística multinomial considerando-se como referência os eutróficos. A prevalência de magreza foi de 8,8% e a de sobrepeso/obesidade de 32,1%. Permaneceram associados à magreza ter anemia e contagem de células TCD4 < 200mm³. Os fatores associados à maior chance de sobrepeso/obesidade foram: idade > 40 anos e presença de diabetes, e aqueles inversamente associados com sobrepeso/obesidade: não ter companheiro fixo, tabagismo, história recente de doença oportunista, anemia e níveis de albumina < 3,5mg/dL. O principal desvio nutricional observado foi o sobrepeso/obesidade, superando a magreza. Os indivíduos mais velhos com diabetes devem ser alvos de intervenções nutricionais e de estilo de vida.